Relationship of Vegetation Distribution to Soil Properties in Kaerkevagge, Swedish Lapland - Darmody, R G; Thorn, CE; Schlyter, P; Dixon, J C (Arctic, antarctic, and alpine research, 2004)
Kaerkevagge, an alpine ecosystem in the subarctic, has been the subject of scientific study for half a century. We investigated the relationship of its vegetation to soil properties. At the lowest elevations, on stable portions of the landscape dominated by Betula and Empetrum, are found Spodosols developed in glacio-fluvial sediments. Cryosaprists occur in scattered bedrock depressions with bog-type vegetation. Cryofluvents are found in flood-prone areas covered by dwarf-willow thickets. Intermediate elevations have meadow-type vegetation with Cryofluvents on floodplains and on lower colluvial slopes, Cryaquents in wetter areas, and Cryorthents on steeper soliflucted slopes. Above that, on steep, west-facing Dryas-covered colluvial slopes, soils are Ca-rich Eutrocryepts and Haplocryolls. The highest-elevation soils are infertile with poor horizonation, despite their possible antiquity, and vegetation that is largely cryptogams. Dystrocryepts occur on more stable alpine locations; Cryorthents on soliflucted areas; and Haploturbels, with shallow permafrost, above 1400 m. Measured annual soil temperatures range from +2.4 degree C at a Dryas site to -3.4 degree C at 1585 m at an alpine cryptogam site. Vegetation distribution in Kaerkevagge is related to climatic factors, which are controlled by elevation and landscape position, and edaphic factors, which control soil moisture and nutrient availability.